Perancangan Smart Card Reader Menggunakan STM32F4 Discovery Kit - Agus Bejo; Mohamad Faiz Hamzah; Addin Suwastono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Smart card has been a new trend as practical and secure authentication solution in online transactions such as epayment, net-banking, e-money, and other online services. The increasing of smart card-based applications demands higher supply of smart card readers as well. Many types of smart card readers in the market have been existed. However, their feature and software are mostly closed and can not be modified to satisfy the application developer’s requirements to optimize the performance and security of the applications. Therefore, a selfdesigned smart card reader is needed to offer flexibility and ability to be costumized in order to satisfy application developer’s needs. In this research, a smart card reader is designed based on 32-bit microcontroller STM32F407VG which is implemented on STM32F4 Discovery Kit. The proposed smart card reader is evaluated by accessing information resides on the JCOP31 smart card which has been pre-installed by applet with certain APDU. Evaluation results show that the proposed smart card reader is able to access smart card properly, having good portability on different platform machines and having good performance as indicated by the CWT and CBT which are faster than the recommended ones.